2020
DOI: 10.1039/d0na00335b
|View full text |Cite
|
Sign up to set email alerts
|

Insights into N, P, S multi-doped Mo2C/C composites as highly efficient hydrogen evolution reaction catalysts

Abstract: N, P, S multi-doped Mo2C/C exhibits highly efficient HER performance, derived from stronger synergistic N, P, S multi-doping coupling effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 55 publications
(77 reference statements)
0
8
0
Order By: Relevance
“…2a, the high-resolution C 1s spectrum includes four distinct peaks located at 284.4 eV, 284.75 eV, 285.5 eV, and 286.7 eV, and they can be indexed to C–Mo, C–C/CC, C–N, and CO, respectively. 39,40 The appearance of the C–N peak further confirms the successful doping of the N element in the carbon skeleton. 41 For the O 1s spectrum (Fig.…”
Section: Resultsmentioning
confidence: 71%
“…2a, the high-resolution C 1s spectrum includes four distinct peaks located at 284.4 eV, 284.75 eV, 285.5 eV, and 286.7 eV, and they can be indexed to C–Mo, C–C/CC, C–N, and CO, respectively. 39,40 The appearance of the C–N peak further confirms the successful doping of the N element in the carbon skeleton. 41 For the O 1s spectrum (Fig.…”
Section: Resultsmentioning
confidence: 71%
“…However, Mo 2 C nanoparticles have some drawbacks, such as easy agglomeration into large particles, which may result in the slow transport of electrons and protons during HER, fewer available active sites due to larger particles size, and relatively poor conductivity compared to the noble metal nanoparticles, hence leading to poor electrocatalytic activity . Several synthetic and nanostructuring approaches have been developed for an advanced electrocatalyst architecture to achieve the full potential of Mo 2 C as an affordable and efficient electrocatalyst. , These include facile one-step and two-step synthesis methods for highly porous Mo 2 C structures, , nanostructuring, , elemental doping, , and hybrid nanostructures. Despite all these efforts, it still remains a challenge to achieve the desired Mo 2 C nanoarchitecture.…”
Section: Introductionmentioning
confidence: 99%
“…1 Several synthetic and nanostructuring approaches have been developed for an advanced electrocatalyst architecture to achieve the full potential of Mo 2 C as an affordable and efficient electrocatalyst. 2,3 These include facile one-step and two-step synthesis methods for highly porous Mo 2 C structures, 4,5 nanostructuring, 6,7 elemental doping, 8,9 and hybrid nanostructures. Despite all these efforts, it still remains a challenge to achieve the desired Mo 2 C nanoarchitecture.…”
Section: ■ Introductionmentioning
confidence: 99%
“…19,20 Because S has similar electronegativity to that of a C atom, it tends to change the spin density rather than the charge density after substitution, enriching the electron density of the Mo centers. 21 Moreover, the S edge exhibits a negative hydrogen adsorption energy, 22 which can accelerate the Volmer reaction. Bearing these two merits in mind, we proposed that introduction of S substitution within MoC may be an effective method for optimizing electronic structures to deliver better HER activity.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the low electron density of Mo in MoC is mainly due to the excessive carbon in the crystal lattice, substituting part of the C with a suitable anion is likely an effective strategy to enhance the hydrogen adsorption process . It is reported that the HER activity of Mo active sites could be improved when the Mo edge is covered with sulfur (S) atoms. , Because S has similar electronegativity to that of a C atom, it tends to change the spin density rather than the charge density after substitution, enriching the electron density of the Mo centers . Moreover, the S edge exhibits a negative hydrogen adsorption energy, which can accelerate the Volmer reaction.…”
Section: Introductionmentioning
confidence: 99%